Reflections on Religious, Cultural, and Political Dynamics in Contemporary Studies - Busro, Busro (UIN Sunan Gunung Djati Bandung, 2024)
This issue of Religious: Jurnal Studi Agama-agama dan Lintas Budaya presents a collection of eight articles that examine the intricate intersections of religion, culture, and politics in Indonesia and beyond. The studies explore a range of topics, including the regulation of religious practices, the politicisation of Islamophobia, the influence of social networks on political behaviour, and the use of digital platforms in preserving cultural values. The issue also delves into local religious responses to agricultural crises and the role of religious identity in fostering social cohesion. Together, these articles contribute to broader discussions on how religious and cultural practices adapt to changing societal contexts, providing valuable insights for researchers, policymakers, and academics.